Biogeography of the Respiratory Tract Microbiome in Patients With Malignant Tracheal Tumors - Liu, Kai-Xiong; Liu, Hai-Xia; Zhang, Jing; Zhang, Nan; Zhou, Yun-Zhi; Tao, Mei-Mei; Wang, Hong-Wu; Qu, Jie-Ming (Frontiers in Oncology, 2021)
Background: This study aimed to characterize the bacterial microbiota in the oral cavity (OC), throat, trachea, and distal alveoli of patients with primary malignant tracheal tumors (PMTT), including squamous cell carcinoma (SCC) and salivary gland carcinoma patients (SGC), for comparison with a matched non-malignant tracheal tumor (NMTT) group. Methods: Patients with pathological diagnosis of PMTT and NMTT were included in this study. Saliva, throat swab (TS), trachea protected specimen brush (PSB), and bronchoalveolar lavage fluid (BALF) samples were collected for 16S rRNA gene sequencing. The composition, diversity, and distribution of the microbiota were compared among biogeographic sampling sites and patient groups. The relationship between the genera-level taxon abundance and tracheal tumor types was also investigated to screen for candidate biomarkers. Findings: The most represented phyla in the four sites were Bacteroidetes, Firmicutes, Proteobacteria, and Fusobacteria. In SCC patients, the relative abundance of Bacteroidetes and Firmicutes gradually decreased with increasing depth into the respiratory tract, while the relative abundance of Proteobacteria gradually increased. Bacterial communities at the four biogeographic sites formed two distinct clusters, with OC and TS samples comprising one cluster and PSB and BALF samples comprising the other group. Principal coordinate analysis showed that trachea microbiota in SCC patients were distinct from that of SGC or NMTT patients. In the trachea, AUCs generated by Prevotella and Alloprevotella showed that the abundance of these genera could distinguish SCC patients from both NMTT and SGC patients. Interpretation: The structure of respiratory tract microbiota in PMTT patients is related to tumor type. Certain bacteria could potentially serve as markers of SCC, although verification with large-sample studies is necessary.